Combination of nuclear magnetic resonance spectroscopy and nonlinear methods to analyze the copolymerization of phosphonic acid derivatives. Issue 48 (18th July 2019) - Heinze, Marcus; Starke, Sandra; Händler, Marcel; Komber, Hartmut; Drache, Marco; Moszner, Norbert; Voit, Brigitte; Pospiech, Doris
ABSTRACT: We demonstrate in this study that the combination of modern inline monitoring methods [here: inline nuclear magnetic resonance (NMR)] with simulations gains more exact and profound kinetic results than previously used methods like linearization without that combination. The 1 H‐NMR spectroscopic data (more than 100 data points) are used to construct the copolymerization diagram. The reactivity ratios are obtained applying the van Herks nonlinear least square method. The examination of the radical copolymerization of 2‐hydroxyethyl methacrylate (HEMA) with (2‐[2‐(ethoxycarbonyl)prop‐2‐en‐1‐yl]oxyethyl) phosphonic acid (ECPPA) as important adhesive monomer used in dentistry yields reactivity ratios of r HEMA = 1.83; r ECPPA = 0.42. The copolymerization diagram reflects nonideal, non‐azeotropic copolymerization. The sequence distribution of the obtained by Monte Carlo simulation indicates the generation of statistical copolymers. As an important finding, it is demonstrated that the repeating units responsible for etching and adhesion are arranged over the whole polymer chain, which is necessary to achieve proper functionality. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48256. Abstract : The kinetics of radical copolymerization of HEMA with phosphonic acid‐containing comonomers was monitored by inline 1 H‐NMR spectroscopy. The reactivity ratios obtained by stochastical method according to van Herk revealed higher reactivity for HEMA and non‐azeotropic copolymerization yielding random copolymers in which the adhesive monomer units are distributed over the whole polymer chain.